2019
DOI: 10.1002/ejoc.201900843
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Opening of Bridged Anhydrides by Amidoximes Providing Access to 1,2,4‐Oxadiazole/Norborna(e)ne Hybrids

Abstract: A unique example of the one‐pot trans‐diastereoselective reaction of meso‐tricyclic anhydrides is reported. The process involves anhydride ring opening by an amidoxime and the sequential cis‐ to trans‐ epimerization/cyclodehydration of the O‐acylamidoxime intermediate. The resulted 1,2,4‐oxadiazole/norborna(e)ne hybrids are obtained in moderate to good yields and > 95 % diastereomeric excess without any additional purifications. These compounds are interesting not only for drug discovery but for other chemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…As mentioned above, the cyclocondensation of O -acylamidoximes is a not so attractive method, and one-pot protocols, which start from amidoximes, are much more desirable, primarily, for drug discovery. The possibility of carrying out the reaction in a “two-step, one-pot” manner is the main advantage of the MOH/DMSO system (M = Li, Na, K) in comparison with TBAF-involved methods, and it was realized in several works [ 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. It is most convenient to discuss these methods by dividing them by the type of used carboxyl function sources: esters, acids, acyl chlorides, anhydrides, dicarboxylic acid anhydrides, aldehydes, and even N -acyl benzotriazoles.…”
Section: Base-induced Cyclodehydration Of O -Acyla...mentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, the cyclocondensation of O -acylamidoximes is a not so attractive method, and one-pot protocols, which start from amidoximes, are much more desirable, primarily, for drug discovery. The possibility of carrying out the reaction in a “two-step, one-pot” manner is the main advantage of the MOH/DMSO system (M = Li, Na, K) in comparison with TBAF-involved methods, and it was realized in several works [ 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. It is most convenient to discuss these methods by dividing them by the type of used carboxyl function sources: esters, acids, acyl chlorides, anhydrides, dicarboxylic acid anhydrides, aldehydes, and even N -acyl benzotriazoles.…”
Section: Base-induced Cyclodehydration Of O -Acyla...mentioning
confidence: 99%
“…The synthesis of 1,2,4-oxadiazole bearing carboxylic functionality via the one-pot condensation of amidoximes and dicarboxylic acid anhydrides is one of the major benefits from the exploitation of the MOH/DMSO medium [ 98 , 99 , 100 , 101 , 102 ]. Notably, successful examples of the base-catalyzed condensation of O -acylamidoximes containing carboxylic functionality are not described.…”
Section: Base-induced Cyclodehydration Of O -Acyla...mentioning
confidence: 99%
See 1 more Smart Citation
“…We have come close to solving this problem by developing methodology to synthesis of 1,2,4-oxadizoles form amidoximes and carboxylic acid derivatives in MOH/DMSO medium at ambient temperature. [34][35][36][37] This approach allows to obtain 1,2,4oxadiazoles with diverse functionalities, including C=C multiple bonds, [38] urea [39,40] and carboxylic substituents, [41][42][43] as well as animo-groups. [44][45][46] It was found that some anilines bearing 1,2,4-oxadiazole moiety intensely emit in the blue region.…”
Section: Introductionmentioning
confidence: 99%
“…The type of the formed heterocyclic core depends mainly on the structure of the electrophile. In particular, the coupling of amidoximes with carbonyl-based compounds such as aldehydes [ 7 , 8 , 9 ], carboxylic acids [ 10 , 11 , 12 ], and their derivatives (esters [ 13 , 14 , 15 , 16 ], anhydrides [ 17 , 18 , 19 , 20 ], as well as acyl chlorides [ 21 , 22 , 23 , 24 ]) usually results in 1,2,4-oxadiazoles. In this case, both nucleophilic centers of amidoxime (NOH and NH 2 groups) attack the same carbon atom of the electrophile ( Scheme 1 A).…”
Section: Introductionmentioning
confidence: 99%